2007
DOI: 10.1038/sj.eye.6702868
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of intraocular foreign bodies in the UK

Abstract: Aims To estimate the incidence of penetrating injuries with retained intraocular foreign bodies (IOFBs) in the United Kingdom, and to provide epidemiological data on the aetiology, management, and visual outcome of such injuries. Methods Cases were identified prospectively by active surveillance through the British Ophthalmological Surveillance Unit reporting card system, for the 12-month period June 2004 to May 2005 inclusive. Questionnaire data were obtained from UK ophthalmologists at presentation and 6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 24 publications
1
24
1
1
Order By: Relevance
“…The incidence of traumatic endophthalmitis after open globe injury with RIOFB ranged from 4.7 to 13.3% (mean = 6.8%) in the literature [2,3,4,5,6,7] and 12% in the current study. Previous reports have demonstrated that the risk of traumatic endophthalmitis increased when ocular injuries were associated with RIOFB and in rural areas [2,3,4].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The incidence of traumatic endophthalmitis after open globe injury with RIOFB ranged from 4.7 to 13.3% (mean = 6.8%) in the literature [2,3,4,5,6,7] and 12% in the current study. Previous reports have demonstrated that the risk of traumatic endophthalmitis increased when ocular injuries were associated with RIOFB and in rural areas [2,3,4].…”
Section: Discussionmentioning
confidence: 93%
“…The early signs of traumatic endophthalmitis may be masked by the concomitant ocular injuries. Ophthalmologists should be alert to the clues and signs of endophthalmitis in these patients [7]. The early diagnosis and treatment of endophthalmitis require a high index of suspicion.…”
Section: Discussionmentioning
confidence: 99%
“…This was a prospective population-based study performed in association with the British Ophthalmological Surveillance Unit (BOSU) monthly reporting system as previously described 13 14. All ophthalmologists with clinical autonomy in the UK receive a monthly reporting card with definitions of the conditions currently under surveillance.…”
Section: Methodsmentioning
confidence: 99%
“…Arka segmente yerleşmiş göz içi yabancı cisimlerin eşlik ettiği göz yaralanmaları genellikle iş kazaları sırasında meydana gelmekte ve en çok gençler ve erkekler bu tür kazalara maruz kalmaktadır. [2][3][4] Çalışmamızdaki hastaların da hepsi erkekti, yaş ortalaması 36.3 idi ve travmaların %70'i iş kazası ile iliş-kiliydi.…”
Section: Discussionunclassified